Genetic Determinants for Bacterial Osteomyelitis: A Focused Systematic Review of Published Literature - Xie, Xiaoping; Li, Jiangbi; Gu, Feng; Zhang, Ke; Su, Zilong; Wen, Qiangqiang; Sui, Zhenjiang; Zhou, Pengcheng; Yu, Tiecheng (Frontiers in Genetics, 2021)
Background: Osteomyelitis is an inflammatory process characterized by progressive bone destruction. Moreover, chronic osteomyelitis is regarded as the difficult-to-treat clinical entity, due to its long-standing course and frequent infection recurrence. Methods: We performed a systematic review to assess the frequency of individual allele and genotype of gene variants among patients with bacterial osteomyelitis and healthy people, in order to identify whether there exists an association between gene polymorphisms and the susceptibility of developing osteomyelitis. Then, GO and KEGG analysis were performed to identify potential biological effect of these genes on the pathogenesis of osteomyelitis. Result: Several eligible studies containing 25 genes were analyzed in this review. According to our review, we discovered the gene polymorphisms in IL1B, IL6, IL4, IL10, IL12B, IL1A, IFNG, TNF, PTGS2, CTSG, VDR, MMP1, PLAT and BAX increased the risk of osteomyelitis, while IL1RN and TLR2 could protect against osteomyelitis. The bioinformatics analysis indicated that these osteomyelitis-related genes were mainly enriched in inflammatory reaction pathways, suggesting inflammation might play a vital role in developing osteomyelitis. Furthermore, functional notation for 25 SNPs in 17 significant genes were performed using RegulomeDB and NCBI databases. Four SNPs (rs1143627, rs16944, rs2430561 and rs2070874) get smaller scores from regulome analysis, implying significant biological function. Conclusion: We systematically summarized many gene polymorphisms linked to osteomyelitis and discovered that these gene polymorphisms could contribute to a genetic factor for osteomyelitis. Moreover, further large scale cohort studies are needed to enhance our comprehensive understanding of developing osteomyelitis, in order to provide earlier personalized preventions and interventions for osteomyelitis patients in clinical practice.